Lattice Boltzmann Simulation of Industrial Axial Fan Noise. Issue 1 (May 2021) - Hayashi, K; Nakaye, S; Nishimura, S
Abstract: Noise simulation of an industrial axial fan has been conducted by implicit large-eddy simulation with Lattice Boltzmann simulation which is based on Cumulant Lattice Boltzmann method with wall model and diffuse-interface method for a moving boundary condition. Simulation results are compared with experimental results of a factory test of an industrial fan for a thermal power generation. The result shows a good agreement and overall value is within 3dB error.